1988
DOI: 10.1037/0021-9010.73.3.497
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and measurement of performance rating accuracy: Some methodological and theoretical concerns.

Abstract: We examined methodological and theoretical issues related to accuracy measures used as criteria in performance-rating research. First, we argued that existing operational definitions of accuracy are not all based on a common accuracy definition; we report data that show generally weak relations among different accuracy operational definitions. Second, different methods of true score development are also examined, and both methodological and theoretical limitations are explored. Given the difficulty of obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(209 citation statements)
references
References 43 publications
3
206
0
Order By: Relevance
“…Appraisal methods are susceptible to many kinds of errors, and human resource experts invest much time to develop and improve the validity o f rating instruments (Barrett & Reman, 1987;Sulsky & Balzer, 1988). The use o f appraisal for academic purpose only, as in this study, does limit the range of limitations in comparison to procedures of performance improvement and personnel decision-making procedures.…”
Section: Evaluation Limitationsmentioning
confidence: 94%
“…Appraisal methods are susceptible to many kinds of errors, and human resource experts invest much time to develop and improve the validity o f rating instruments (Barrett & Reman, 1987;Sulsky & Balzer, 1988). The use o f appraisal for academic purpose only, as in this study, does limit the range of limitations in comparison to procedures of performance improvement and personnel decision-making procedures.…”
Section: Evaluation Limitationsmentioning
confidence: 94%
“…Specifically, Schoorman (1988) reported that supervisors who had a say in the hiring decision and who viewed the applicant as favorable, subsequently tended to give lenient performance ratings while those who participated in hiring but viewed the applicant as unfavorable, tended to give more severe ratings. Finally, Sulsky and Balzer (1988) argued that accuracy in performance measurement was lacking due to poor definitions of accuracy, methodological and theoretical limitations of true score development, and the absence of a cohesive theory of performance.…”
Section: Rating Errors and Accuracymentioning
confidence: 99%
“…For example, Bernardin and Pence (1980) reported that raters who were trained to reduce halo error actually made less accurate ratings after training. Similarly, Sulsky and Balzer (1988) discussed the uncertain relationship between inter-rater reliability, rating errors, and accuracy in performance appraisal because of our inability to know what`truth' is. Low interrater reliability is thus evidence of disagreement in making judgments.…”
Section: Discussionmentioning
confidence: 99%